Integrated Instructional Approaches to Foster Critical Thinking in Science Teacher Education: A Systematic Literature Review - Samsuri, Taufik; Santosa, Made Hery; Sudatha, I Gde Wawan; Suartama, I Kadek; Fitriani, Herdiyana (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study presents a systematic literature review of recent research on the impact of integrated instructional approaches in strengthening critical thinking skills among prospective science teachers. Through an in-depth analysis of selected publications, the findings indicate that reflective learning strategies such as explicit rubric-based simulations, argument mapping, journaling, project-based learning, and the integration of socio-scientific contexts consistently enhance the cognitive, metacognitive, and affective dimensions of critical thinking. The review further demonstrates that emotional engagement and metacognitive awareness function as essential conditions for the effectiveness of reflective instruction. In addition, embedding local cultural contexts is shown to increase the relevance and meaningfulness of science learning. From a practical perspective, these findings imply that teacher education programs should systematically integrate reflective instructional designs, formative assessment rubrics, and culturally responsive learning tasks into their curricula. Moreover, institutions are encouraged to strengthen lecturer professional development, improve digital learning infrastructure, and adopt flexible curriculum policies to address implementation challenges such as institutional resistance and variability in student engagement. Collectively, these implications support the development of adaptive, inclusive, and context-sensitive science teacher education aligned with the demands of 21st-century learning.